Heavenly Sanctuary Mysticism in the Epistle to the Hebrews - Mackie, Scott D. (The journal of theological studies, 2011)
This essay focuses on the supernatural experiential elements and events that attend the Epistle to the Hebrews’ portrayal of the heavenly sanctuary, and attempts to demonstrate the integral relationship of these elements and events to the author’s overarching hortatory effort. Hebrews’ narratival construction of the heavenly sanctuary is not simply an ‘updated and expanded’ version of the tradition, intended to stir the addressed community’s imagination; rather, the author’s goal is for the community actually to be present in that sacred place, to benefit truly from Christ’s actions performed there, and to participate in the Son’s exaltation. Their presence and participation is effected via the author’s repeated calls to ‘draw near’ and enter the heavenly sanctuary (4:14–16; 6:18–20; 10:19–23; 12:22–4), which have as their goal a transformative encounter with God and his Son, as well as their involvement in a divine adoption ceremony (2:12–13). Mystical visuality, working in concert with the rhetorical practices of ekphrasis and enargeia, together provide crucial assistance to this effort: besides a number of vivid descriptions of the heavenly sanctuary and Jesus’ sacral actions therein, the author exhorts the community to ‘see’ the exalted Son (2:9; 3:1; 9:24–6; 12:2) and their involvement in the adoption ceremony (2:13; 10:24–5). This visual programme directly serves the author’s ultimate hortatory purpose: just as Moses ‘persevered by seeing him who is invisible’ (11:27), so also the community’s waning commitment will be reversed when they actualize their true identity as the family of God, and ‘see’ in Jesus that their steadfastness in suffering will surely result in vindication (2:6–10).